(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Wayang Wong is one of UNESCO’s intangible cultural heritage that has an important function, as a communication medium in conveying moral messages to the community, conveying social, spiritual and philosophical values for the Javanese Society. However, the development of globalization and cultural tourism encourages commodification where the sacral function of performance shifts to entertainment products and economic commodities. Digital transformation also accelerates the process through the use of social media, online performances and content distribution based on digital platforms. The results of this study see that digitalization will affect the form, meaning and function of wayang wong in the context of cultural tourism by placing on the debate between nation-building and digital neocolonialism. The research method used is a case study with a qualitative approach involving wayang wong sriwedari as the object of study. Data were collected through in-depth interviews, direct observations, and literature studies. The analysis uses the framework of Vincent Mosco’s communication economics and political theory, especially in the aspects of commodification of message content, commodification of workers and commodification of audiences. The results of the research show that digitalization provides opportunities to expand audience access to become global and increase economic value for some art actors. However, on the other hand, there is a reduction in philosophy and meaning in the performance due to the adaptation in digital format and the use of Youtube, Instagram, TikTok which has the potential to create a new space for wayang wong sriwedari performances. This also causes local communities to be vulnerable to the logic of the digital market, so it can be read as a form of neocolonialism in the cultural industry.